(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Progressive myoclonic epilepsy (PME) is an epilepsy syndrome characterized by myoclonus, cognitive deficit and ataxia. Common PMEs are Unverricht–Lundborg disease, myoclonic epilepsy with ragged-red fiber (MERRF) syndrome, Lafora body disease, neuronal ceroid lipofuscinoses, and sialidases. This study was conducted to obtain baseline information on PME in terms of phenotype, EEG, MRI of the brain, and overall genetic profile. Methodology: This retrospective observational study was conducted in the Department of Pediatric Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. The duration of the study was from January 2020 to December 2023. Children diagnosed as PME on the basis of phenotype, EEG, imaging and genotype were included in this study. The genetic diagnosis was done by next-generation sequencing. Result: A total of 11 patients were analyzed in this study. The age of onset ranges from 6 months to 5 years. Consanguinity of the parents was present in 8 cases; one patient had a positive family history of a similar type of illness. The key clinical features were seizure, ataxia, neuroregression, visual impairment, dystonia etc. EEG features showed focal epileptic discharges (6), generalized discharges (5), with progressive deterioration of background in most of the cases. In MRI, 8 out of 11 patients had cerebello-cerebral atrophy. In all cases, next-generation sequencing was done; of them, three cases had KCTD7 gene mutation, three had CLN6 gene mutation causing Neuronal ceroid lipofuscinosis, another three had TPP1 gene mutation and the remaining two had MFSD8(-) gene mutation. Conclusion: This study will highlight the pattern of genotype and phenotype of children with PME in Bangladesh. J Bangladesh Coll Phys Surg 2025; 43: 269-276